Hepatitis B sero-prevalence among blood donors in Haryana: a retrospective record based study - Sehgal, P. K.; Garg, Anubha (International Journal of Research in Medical Sciences, 2017)
Background: In India, it is mandatory to screen blood donors for HIV, hepatitis B, hepatitis C, syphilis and malaria. Hepatitis B is a major public health problem worldwide. Approximately 30% of the world’s population or about 2 billion persons have serological evidence of either current or past infection with hepatitis B virus. The prevalence of chronic HBV infection in India ranges from 2% to 10% as shown by different studies. India therefore comes under the intermediate to high endemicity category. The objective of this study was to carry out with the aim to find out the sero-prevalence of hepatitis B infection and its trend among the blood donors a hospital based blood transfusion service set up in north India over a period of seven years. Methods: It was record based retrospective study from 2007 to 2013. Before donation "Blood Donation Form" had been filled by every donor and this form had particulars about age, gender, address, and occupation, date of previous donation, any illness and medical treatment taken. The donor blood samples were collected at the time of blood donation from the primary bag and HbsAg screening was done using rapid test kit based on the principle of a one-step immunoassay. Samples showing repeat test reactivity on both methods were considered positive and were included for calculation of seroprevalence. Results: A prevalence of 01.13% of hepatitis B infection was seen among the donors from the period 2007-2013. The trend of hepatitis B prevalence among donors has been fluctuating while ranging from 0.94% to 1.63%. Conclusions: Reduction in seroprevalence among voluntary donors requires an effective donor education and high quality selection programme especially during big blood donation camps. For a safe blood service in our country, where comprehensive laboratory tests are neither possible nor pragmatic, it is best to switch over to 100% voluntary donations, as it is now established that only voluntary non-remunerated regular donation is the safest. Thus, one of our key strategies to enhance blood safety is to focus on motivating non-remunerated blood donors and phasing out even replacement donors.